Disposition time of major trauma patient at Emergency Department HUSM Kelantan. - Rosman, Roshidah (2011)
Introduction This is a cross-sectional observational study over a period of 7 months from December 2009 to June 2010 looking at the mean disposition time of major trauma patient in Emergency Department (ED) HUSM Kelantan. Objectives The objectives of this study were to determine the mean disposition time of major trauma patient and to determine the factors affecting disposition time of major trauma patient in Emergency Department HUSM Methodology The study was conducted at Red Zone Emergency Department HUSM. Inclusion criteria was patient with Injury Severity Score >15. This study was approved by the Ethical Committee on 3rd June 2009. Patients’ clinical parameters, injury characteristics, ED interventions and radiological investigations were documented in data entry form.The time interface for every patient from the time of arrival to the disposition time. Results Seventy patients were recruited in this study. Mean ED resident response time was 2.7 minutes (sd= 2.2). While mean specialty unit response time is 45.7 minutes (sd= 35.7). Mean disposition time of major trauma patient is 272.7 minutes (sd= 200.1) Multiple comparisons of disposition unit using one-way ANOVA showed a statistical difference between the groups. ICU disposition time (mean 369.18 minutes, sd=287.58) was significantly different from the OT disposition time (mean 209.25 minutes, sd=86.89) and the mortuary disposition time (mean 154.6 minutes, sd=94.21). Patient’s systolic blood pressure (SBP) and oxymetry were noted to correlate with the disposition time with r=0.237 and r=0.244 respectively, p<0.05. Conclusion This study showed that major trauma patient were managed for 209 minutes in ED prior to operative care and 369 minutes before sending to ICU.